2002
DOI: 10.1161/hc0602.103724
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Inhibitor W-7 Unmasks a Novel Electrocardiographic Parameter That Predicts Initiation of Torsade de Pointes

Abstract: Background-We have shown that the calmodulin inhibitor W-7 suppresses torsade de pointes (TdP) without shortening the QT interval, which is consistent with other findings that QT prolongation, per se, is insufficient to generate TdP. ECGs were analyzed from a well-characterized animal model of TdP to identify more reliable predictors of this life-threatening ventricular arrhythmia. Methods and Results-TdP was induced using methoxamine and clofilium in 12 of 14 rabbits pretreated with vehicle control, whereas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 43 publications
2
57
1
Order By: Relevance
“…In these experiments the increased SBVR better predicted the development of TdP arrhythmia than repolarization prolongation alone [3,4,19,20]. Hinterseer et al published similar findings in selected human patients [21] and it is also known that the successful antiarrhythmic treatment does not need to be accompanied by QT interval shortening [22,23]. These results question the association between QT prolongation and the arrhythmia development.…”
Section: The Short Term Beat-to-beat Variability Of Cardiac Action Pomentioning
confidence: 98%
“…In these experiments the increased SBVR better predicted the development of TdP arrhythmia than repolarization prolongation alone [3,4,19,20]. Hinterseer et al published similar findings in selected human patients [21] and it is also known that the successful antiarrhythmic treatment does not need to be accompanied by QT interval shortening [22,23]. These results question the association between QT prolongation and the arrhythmia development.…”
Section: The Short Term Beat-to-beat Variability Of Cardiac Action Pomentioning
confidence: 98%
“…W-7: Increased activity of calmodulin after prolongation of repolarization has been implicated as a cause of afterdepolarizations in many studies, and the calmodulin antagonist W-7 has been demonstrated to prevent TdP initiated by coadministration of methoxamine and clofilium in anesthetized rabbit. 15,16) Unexpectedly, our results show that W-7 expedites the onset of TdP and can not protect dofetilide-induced TdP in conscious rabbits with heart failure. It might be possible that the altered kinetics of calmodulin in heart failure are different from those in normal hearts, which in turn may have consequences for the induction of VPD and TdP.…”
Section: Prevention Of Dofetilide-induced Tdp By Verapamil Ryanodinementioning
confidence: 62%
“…The doses of dofetilide and pretreated compounds were chosen based on the findings of previous publications. 5,7,[14][15][16][17]20) Statistics: Values are expressed as the mean ± SEM and n indicates the number of animals. Student's t test and one-way analysis of variance (ANOVA) were applied when appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this hES-CMC system, we record the field potential duration (FPD)-as QT-like intervals-of clusters treated with a compound; we then calculate the corrected FPD (FPDc) and examine whether or not the compound prolongs FPDc. However, there have been reports that the QT interval is not a good surrogate marker of TdP and ventricular fibrillation [9][10][11][12][13][14][15][16][17][18]; the beat-to-beat variability of QT or QTc is suggested to be a better parameter [14,15]. It would therefore be of interest to investigate whether short-term variability in FPDc (STV FPDc ), as beat-to-beat variability, is increased along with FPDc prolongation in hES-CMCs treated with torsadogenic agents.…”
Section: Introductionmentioning
confidence: 99%